2016
DOI: 10.4038/mljsl.v4i2.7336
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse in Puttalam, Sri Lanka: a medico-legal analysis

Abstract: Introduction: All cases of child sexual abuse (CSA) are expected to be examined by specialists in Forensic Medicine in Sri Lanka. Further, management should not be confined to medico-legal aspects but ensure the psychosocial management of child and family. Therefore, this study was conducted to identify and describe patterns of abuse and strategies of management of children affected with CSA. Methods: Retrospective descriptive study was conducted on all the victims of child sexual abuse reported to Base Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…These findings may be due to an increase in the prevalence of CSA or may reflect increased public awareness of CSA. However, the number of cases who presented in our study is much less than that of Northern (352 cases over a 6 year period) and North Western (183 cases over 18 months) areas of the country 11,14,15 . Further studies should be done to identify reasons for variation of the rates of CSA in different parts of the country.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These findings may be due to an increase in the prevalence of CSA or may reflect increased public awareness of CSA. However, the number of cases who presented in our study is much less than that of Northern (352 cases over a 6 year period) and North Western (183 cases over 18 months) areas of the country 11,14,15 . Further studies should be done to identify reasons for variation of the rates of CSA in different parts of the country.…”
Section: Discussioncontrasting
confidence: 58%
“…A higher prevalence has been reported in Northern Sri Lanka, an area which has been affected by the civil war 8 and in areas associated with the tourism industry 9 . Hospital based studies have shown a wide variation in the number presenting to hospitals with alleged abuse, with numbers ranging from 84 cases over 15 years (average 5.6/year) 10 to 183 over 18 months (average 122/year) 11 . Although CSA is prevalent in Sri Lanka, studies examining victim and perpetrator characteristics, risk factors for abuse, pattern of disclosure and psychological impact of abuse are limited in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…In Sri Lanka, many researchers have focused only on the characteristics and descriptive statistics of CSA. There are some studies that detect the key risk factors using chi-square tests and logistic regression Amararatne et al (2016) , Chandrasiri et al (2017) , Sathiadas et al (2018). But none of the studies have used ordinal logistic regression models nor machine learning techniques to detect the key risk factors of CSA and to predict the severity of CSA in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%